2022
DOI: 10.1088/1755-1315/974/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of three types of pheromones against Rhynchophorus vulneratus (Panzer) and Oryctes rhinoceros (L.) in Indonesia

Abstract: Rhynchophorus vulneratus and Oryctes rhinoceros are two major pests that cause serious damage to coconut palms leading to a significant coconut yield loss. Several pheromones have shown the potential as lures for these insect pests. This study aimed to measure the effectiveness of Oricmas, Rhynchomonas, and Feromonas, the three types of pheromones, against R. vulneratus and O. rhinoceros. In this study, traps baited with each pheromone were installed at the four Research Stations of IPCRI in North Sulawesi, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In general, the sex ratio of the captured weevils was also close to a 1:1. In contrast to this result, Hosang et al [14] found a higher ratio of female R. vulneratus (2:1) attracted to the 4methyl-5-nonanol trap, which was installed in the coconut plantation on Sulawesi island. The difference is probably due to the higher beetle population found in the coconut plantation in Sulawesi, which provides abundant food sources.…”
Section: Figure 3 the Average Number Of Captured Weevils Per Pherotra...mentioning
confidence: 74%
“…In general, the sex ratio of the captured weevils was also close to a 1:1. In contrast to this result, Hosang et al [14] found a higher ratio of female R. vulneratus (2:1) attracted to the 4methyl-5-nonanol trap, which was installed in the coconut plantation on Sulawesi island. The difference is probably due to the higher beetle population found in the coconut plantation in Sulawesi, which provides abundant food sources.…”
Section: Figure 3 the Average Number Of Captured Weevils Per Pherotra...mentioning
confidence: 74%
“…A population of 5 insects on 1 hectare of coconut plantation harms production quantity by up to 50-100% [2]. Symptoms of damage caused by larvae are not easily detected and cause greater damage because the next larval instar will damage plant roots or grows on organic material [3]. O. rhinoceros beetle spreads to almost all provinces in Indonesia where oil palm plants grow and the volume of organic material in the field serves as a breeding ground and food for the larvae.…”
Section: Introductionmentioning
confidence: 99%